Screening of Lipase-Producing Microbes for Oil Bioremediation: An Eco-Friendly Approach (International Journal of Scientific Research in Science and Technology, 2025)
Oil pollution poses significant environmental challenges, threatening ecosystems and human health. Microbial lipases offer eco-friendly solutions for degrading lipid-based pollutants. Microbial lipases (EC 3.1.1.3) are versatile enzymes capable of catalysing lipid hydrolysis and synthesis, with significant potential for industrial and environmental applications. This study aimed to explore the bioremediation potential of microbial lipases obtained from dairy products, oil-contaminated soil and water, garage soil, and mill effluents. Lipase activity was optimized under varying pH, temperature, and incubation conditions. Optimal activity was observed at pH 6, temperatures of 37°C, and incubation time 60 min. Among the isolates, Mill Water Enzyme showed the highest specific activity (7.02 U/mg), whereas garage soil enzyme exhibited the highest bioremediation efficiency (0.0687 U/mol). Bioremediation assays using the gravimetric method showed promising results. The Mill Soil, Garage Soil, and Dairy Water Enzymes achieved 50% oil degradation from soil, whereas the Mill Water, Mill Soil, and Garage Soil Enzymes achieved 100% oil degradation from water effluent. Similarly, the Mill Water Enzyme demonstrated complete oil degradation (100%) in the dairy waste water effluent. Titrimetric estimation further underscored the effectiveness of microbial enzymes in oil breakdown, with garage soil enzyme exhibiting the highest activity (0.0687 U/mol). This study confirms the industrial and environmental relevance of microbial lipases, particularly in bioremediation.